Cold in-place recycling for flexible pavements - Ahmad Kamil, Arshad; Ekarizan, Shaffie; Fauzilah, Ismail; Putra Jaya, Ramadhansyah (Universiti Malaysia Perlis, 2020)
CIPR is an economical and environmentally sound alternative to conventional rehabilitation methods such as structural overlay or reconstruction. The reuse of existing pavement materials is a sustainable approach to pavement rehabilitation as new materials are conserved. Its use in Malaysia is expected to increase in the future as more pavement rehabilitation works instead of new roads construction will be carried out to preserve the integrity of the pavement structure and to extend the pavement life. However, an adequate understanding of the CIPR process, its suitability and limitations are essential for the correct pavement candidate to be chosen, for the works to be carried out successfully and for the pavement to perform satisfactorily.